PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV DI SDN 4 CILEGON - Jamah Dinih Tawana, - (2022)
Education can affect the quality of human resources because it has an important role, one of which is Social Science education. Teachers have an important role in learning activities because they are responsible as facilitators to stimulate, guide, and increase students' knowledge. The results of the researcher's observations became the background of this study which stated that the learning activities were centered on the teacher because conventional methods were still being used. As a result, learning activities in the classroom tend to be passive so that the learning objectives are not achieved and have an impact on the achievement of student learning outcomes. Therefore, teachers should be more creative in choosing learning models and in accordance with the characteristics of elementary school students, namely children like to play so that learning activities are interesting, students become active, and learning objectives are achieved optimally. The learning model is a cooperative learning model of the TGT type which is in accordance with the characteristics of elementary school children, contains elements of games that will help student become materially literate and have eager to learn. The purpose of this research is to improve the social studies learning outcomes for fourth grade students by applying the TGT learning model to social studies learning. This study uses a qualitative approach with classroom action research method and consists of 2 cycles. In the first cycle of research, students got an average score of 65.74 and the percentage of students' completeness was 48.15%. The second cycle of research increased, namely students got an average score of 80.14 and the percentage of student achievement was 74.1% and had succeeded in achieving the expected results. The results of this study indicate that the TGT learning model can improve students' social studies learning outcomes.